2020
DOI: 10.3389/fpsyg.2020.02044
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Maternal Emotion Socialization: Based on Belsky’s Process of Parenting Model

Abstract: The purpose of the current study was to investigate how the potential multifactors influence mothers' emotion socialization. This study involved 300 Japanese-speaking married mothers with 2-5-year-old children, who answered a series of measures of emotion socialization (coaching, dismissing, dysfunction, and non-involvement), emotion regulation strategy (reappraisal and expressive suppression), psychopathology (anxiety and depression), and perceived parenting alliance with their partners. (a) Hierarchical mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The research demonstrated that cognitive reappraisal is positively associated with using praise in interactions 28 , supportive emotion socialisation 29 and can moderate maternal anger towards young children 30 , while, emotional suppression is negatively related to parental guidance, warmth and responsiveness in parent–child interactions 31 . In a recent study, cognitive reappraisal was positively and expressive suppression was negatively associated with supportive strategies (i.e., coaching) in Japanese mothers of 2–5-year-old children 32 . In the same study, both emotion regulation strategies and mental health symptoms were related with emotion socialisation.…”
Section: Introductionmentioning
confidence: 92%
“…The research demonstrated that cognitive reappraisal is positively associated with using praise in interactions 28 , supportive emotion socialisation 29 and can moderate maternal anger towards young children 30 , while, emotional suppression is negatively related to parental guidance, warmth and responsiveness in parent–child interactions 31 . In a recent study, cognitive reappraisal was positively and expressive suppression was negatively associated with supportive strategies (i.e., coaching) in Japanese mothers of 2–5-year-old children 32 . In the same study, both emotion regulation strategies and mental health symptoms were related with emotion socialisation.…”
Section: Introductionmentioning
confidence: 92%
“…We hypothesized that parents who utilized greater cognitive reappraisal and less expressive suppression would demonstrate higher PSE. We further hypothesized that positive relations between cognitive reappraisal and PSE would be more pronounced among parents with higher-quality coparenting relationships (Bao & Kato, 2020), whereas negative relations between expressive suppression and PSE would be mitigated among parents with higher-quality coparenting relationships. Additionally, we anticipated the moderating effect of coparenting on relations between parent ER and PSE would be more pronounced in fathers compared to mothers, in accordance with the father vulnerability hypothesis (Goeke-Morey & Cummings, 2007).…”
Section: The Present Studymentioning
confidence: 99%
“…However, parenting quality more strongly decreased child emotional negativity in families with higher-quality coparenting relationships. In a sample of Japanese mothers of toddlers and young children, mothers who relied on cognitive reappraisal were more likely to “coach” their children’s emotions (e.g., soothe, validate child’s emotions, provide coping strategies) when mothers reported lower-quality parenting alliances (Bao & Kato, 2020). Thus, while prior research has supported the role of coparenting as a key moderator in the family system, previous studies have not considered its role in associations between parent ER and PSE.…”
Section: Introductionmentioning
confidence: 99%
“…Among mothers in a low socio-economic community sample, difficulties in emotion regulation predicted overall dysfunctional parenting behavior and overreactivity, while substance use and trauma-associated and depressive symptoms had no significant contribution (Powers et al, 2021). Bao and Kato (2020) studied the association between specific emotion regulation strategies and emotion socialization in mothers from a community sample controlling for symptoms of anxiety and depression. They found reappraisal strategies to be related to more supportive emotion socialization (coaching) and fewer unsupportive emotion socialization (dismissing).…”
Section: Elevated Level Of Psychopathologymentioning
confidence: 99%